Employing the organizational culture dimensions to reduce the cases of emotional attrition of employees: An exploratory/ Analytical study of the opinions of a sample of employees in the Maysan Health Department - Hayder Resen, Salem (Iraqi Journal for Administrative Sciences, 2024)
The research aims to measure the possibility of employing the components of organizational culture to reduce emotional attrition among employees at the level of the Health Department in Maysan, Based on a basic problem embodied in several questions that included the extent of awareness of the correlation and influence relationships between the research variables, A model (Gordon, 1993) was adopted to measure the organizational culture variable. A model (Demerouti et al. 2010) was adopted for emotional depletion, which is a one-dimensional variable. The research was applied to a sample that included (141) employees in the Maysan Health. In addition, the questionnaire tool was used as a main tool for data collection and the Cronbach Alpha analysis was used to ensure the stability of the Questionnaire . In addition to using statistical methods, which are the arithmetic mean, the standard deviation, Regression analysis and t-test, to display the statistical aspect. The research also reached conclusions, the most important of which is that organizational culture has an effective role in reducing emotional exhaustion. As for the most important recommendations, the work was to open certain centers to deal with the negative psychological effects of emotional depletion.